Komodifikasi Praktek Yoga sebagai Simbol Figural Pada Masyarakat Urban - Malini, Kadek Hema (Widya Sandhi, 2018)
Yoga becomes a popular culture especially after yoga is recognized by the world with the establishment of World Yoga Day. The meaning of yoga teachings which are then well appreciated by the community makes yoga a culture that is unstoppable in its development. Understanding the benefits of yoga practice makes yoga a new culture among the rapidly growing urban community. Yoga is interpreted and accepted as a representation of the purpose of life and harmony of human life in the community. But yoga today has undergone a change of concept from sacred to profane as the impact of the cultural industry which involves itself in the form of sophisticated ideological indoctrination by using entertainment as a sweetener in the process of changing the existing order. Yoga has been de-contextual from its original understanding because of the influence of the lifestyle and consumer culture of the urban community. Yoga becomes a culture that undergoes decontextualization, simulation, reduplication and is constantly being renewed and experiencing restylization.